Precise model of LC active power filter and feedback linearization control. Issue 1 (1st May 2022) - Ou, Zuoyuan; Wang, Yingpin; Su, Chang; Qu, Yi; Peng, Hongyan; Hao, Xuguang
Abstract: The problems of regulating power quality are more prevalent. In general, Active power filter(APF) is one of the best solution. But the influence of load impedance and grid impedance were widely ignored by a great number of papers, supposed the load voltage is constant and modeling in APF singly, which can't describe the system accurately. Firstly, there are build an accurate model, including LC APF, load and grid impedance. Secondly, applying feedback linearization and proportional resonant differentiation (FL-PRD) control in inner current loop. Then analyze the influence of load and grid impedance. Once more, checked the accuracy of builded accurate model by Simulink and experiment. Eventually, compare mentioned algorithm in the paper with classical proportional resonant (PR) controller. The results show that it is rather important to set up an accurate model and the proposed algorithm gets a perfect capacity.